The State between fact and law: the role of recognition and the conditions under which it is granted in the creation of new States (Polish Yearbook of International Law, 2016)
This article explores the role of recognition in State creation. Basing on an analysis of relations between effectiveness and legality in the process of State creation, it claims that recognition is constitutive of statehood as a subject of international law. The research revolves around the following themes: the role of effectiveness criteria and the conditions of recognition set by international law, the existence of “statehood without effectiveness” in cases of limited effectiveness but general recognition, the study of acquisition of statehood as a process and the notion of collective recognition based on the cases of Kosovo and Palestine. The argumentation is also supported by the analysis of de facto entities and aspiring States in international practice. It draws on the distinction between legal non-recognition and political non-recognition as able to shed some light on the complexity of international practice in this area. The article concludes that recognition is a pre-requisite of statehood, an essential criterion that may overcome weak effectiveness in certain legal contexts, though not a lack of independence. Conversely, effectiveness of government authority over population and territory does not lead to statehood in the meaning of international law in the absence of international recognition.